2013
DOI: 10.1155/2013/739432
|View full text |Cite
|
Sign up to set email alerts
|

Fully Endoscopic Microvascular Decompression: Our Early Experience

Abstract: Background. Microvascular decompression (MVD) is a widely accepted treatment for neurovascular disorders associated with facial pain and spasm. The endoscope has rapidly become a standard tool in neurosurgical procedures; however, its adoption in lateral approaches to the posterior fossa has been slower. The endoscope is used primarily to assist conventional microscopic techniques. We are interested in developing fully endoscopic approaches to the cerebellopontine angle, and here, we describe our preliminary e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
27
0
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(36 citation statements)
references
References 13 publications
3
27
0
3
Order By: Relevance
“…This transition from MVD to E-MVD has been detailed in a prior paper from our group. 7 In the last full year, from August 2012 to July 2013 (representing 35 cases), microscopic MVD was only performed in 1 case because the endoscope-holding arm was not physically available. This absence was identified prior to the start of surgery.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…This transition from MVD to E-MVD has been detailed in a prior paper from our group. 7 In the last full year, from August 2012 to July 2013 (representing 35 cases), microscopic MVD was only performed in 1 case because the endoscope-holding arm was not physically available. This absence was identified prior to the start of surgery.…”
Section: Resultsmentioning
confidence: 99%
“…2,7,11,21,24 All report excellent safety and short-to medium-term functional results. The largest of these, by Kabil et al, reported results for 255 patients with a favorable 3-year success rate and a lower rate of complications when compared with published series of microscopic MVD.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…In this way, a new procedure or new treatment for patients with refractory facial pain can be validated and hopefully approved. 17,23 Fortunately, patients with TN have had great success with microvascular decompression, Gamma Knife treatment, and glycerol rhizotomy; however, patients with atypical facial pain continue to suffer from a lack of validated treatment options.…”
Section: Future Directionsmentioning
confidence: 99%
“…[5][6][7][8] More recently, endoscopic approaches have been developed for use in lateral skull-base surgery, and in particular, in the surgical treatment of trigeminal neuralgia. [9][10][11] In this article, the fully endoscopic microvascular decompression (E-MVD) for patients with trigeminal neuralgia is discussed.…”
Section: Introductionmentioning
confidence: 99%